Urgensi Akreditasi Perguruan Tinggi di Indonesia - Ihsan, Muh.; Mahmud, Muchammad Eka (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
Accreditation is the determination of quality standards and assessments of an educational institution (higher education) by parties outside independent institutions. Accreditation is also interpreted as a government effort to standardize and ensure the quality of university alumni so that the quality of graduates between universities is not too varied and according to work needs. This research aims to explore more broadly the meaning and urgency of higher education accreditation. The approach used in this study is a literature review. The data collected comes from various related documents such as journals, books and other related documents. The findings in this study are more oriented to the disclosure of the meaning and urgency of higher education accreditation. That the results of university accreditation are useful in providing official recognition to universities, which can increase the reputation and public trust in the institution. This is important in attracting prospective students, teachers, and partners. Then access to funding; The number of financial institutions and funding organizations requires universities to have accreditation as a condition for obtaining funding or grants. The implications of the research lie in the limitations of methodology and limited data around the urgency of university accreditation.